Safety and efficacy of microwave ablation for abdominal wall endometriosis: A retrospective study - Liu, Yujiang; Wen, Wanwan; Qian, Linxue; Xu, Ruifang (Frontiers in Surgery, 2023)
OBJECTIVES: This retrospective study aimed to evaluate the safety and feasibility of ultrasound-guided microwave ablation in the treatment of abdominal wall endometriosis (AWE). BACKGROUND: AWE is a rare form of endometriosis that often results in cyclic abdominal pain. The current treatment algorithm for AWE is not well established. Microwave ablation technology is a promising new thermal ablation technique for treating AWE. METHODS: This was a retrospective study of 9 women with pathologically proven endometriosis of the abdominal wall. All patients were treated with ultrasound-guided microwave ablation. Grey-scale and color Doppler flow ultrasonography, contrast-enhanced ultrasonography, and magnetic resonance imaging were used to observe the lesions before and after treatment. The complications, pain relief, AWE lesion volume, and volume reduction rate were recorded 12 months after treatment to evaluate the treatment efficacy. Complications were classified according to the Common Terminology Criteria for Adverse Events and the Society of Interventional Radiology classification system. RESULTS: Contrast-enhanced ultrasound showed that all lesions underwent successful treatment with microwave ablation. The average initial nodule volume was 7.11 ± 5.75 cm3, which decreased significantly to 1.85 ± 1.02 cm3 at the 12-month follow-up with a mean volume reduction rate of 68.77 ± 12.50 %. The periodic abdominal incision pain disappeared at 1 month after treatment in all 8 patients. The adverse events and complications were Common Terminology Criteria for Adverse Events grade 1 or Society of Interventional Radiology classification grade A. CONCLUSIONS: Ultrasound-guided microwave ablation is a safe and effective technique for the treatment of AWE, and further study is warranted.